BLOCKCHAIN FOR DIGITAL CERTIFICATION: A SYSTEMATIC REVIEW OF SECURITY, INTEROPERABILITY AND ADOPTION IN INDONESIAN HIGHER EDUCATION - Alim Hardiansyah; Mohammad Ahmad Bani Amer (CV. ADIBA AISHA AMIRA, 2026)
The forgery of academic diplomas and certificates is a chronic problem that undermines the credibility of Indonesian higher education, whilst conventional centralised verification systems have proven to be vulnerable to manipulation, inefficiency, and single points of failure. This article presents a systematic review of the potential of blockchain technology as a secure, interoperable, and widely adoptable digital certification infrastructure in Indonesian higher education. The research method employed in this study is a literature review. The findings indicate that blockchain significantly enhances the integrity of academic credentials through asymmetric cryptographic mechanisms, immutable hash functions, and a distributed architecture that eliminates the need for a central verification authority. Cross-institutional and cross-border interoperability is ensured by global standards such as Blockcerts and W3C Verifiable Credentials, which enable lifelong credential portability. However, adoption in Indonesia remains hindered by digital infrastructure disparities across regions, a shortage of blockchain-competent human resources, regulatory uncertainty regarding the legal validity of digital diplomas, and organisational cultural resistance. This article recommends a three-phase implementation roadmap—pilot (2026–2027), scaling (2028–2029), and maturity (2030+)—which requires national coordination through a higher education blockchain consortium, strategic investment in human resource capacity building, and regulatory harmonisation to establish legal certainty. With a holistic and collaborative approach, Indonesia has the opportunity to become a regional leader in blockchain-based digital certification, realising a higher education ecosystem that is transparent, accountable, and globally competitive.